MULTIPLICATION EXAMINATION OF TURMERIC EXPLANTS USING AUXIN AND CYTOKININ TO MODIFIED MEDIA - Nur Azizah Romadhoni; Erni Suminar; Anne Nuraini; Syariful Mubarok (Jurnal Penelitian Saintek, 2019)
This study was aimed at obtaining the type and concentration of cytokines as well as the optimal concentration of auxin for the multiplication of turmeric shoots in vitro. The trial was conducted in September 2017 until February 2018 at the Tissue Culture Seed Technology Laboratory of the Faculty of Agriculture, Padjadjaran University. The materials used in this study were Murashige and skoog modified multiplication medium, jelly, sterile distilled water, HgCl2, 70% alcohol, clorox, tween 80 and fungicide and bactericidal. Growth Regulating Substances (GRS) used are BAP, TDZ, Zeatin and NAA. The explant source used was derived from the shoot of turmeric clones from Bogor. The experimental design in this study was Completely Randomized Design (CRD) with seven treatments and four replications. The planting medium used was Murashige Skoog Modification (MS) with the addition of Benzyl Amino Purine (BAP) 9 mg L-1, Thidiazuron (TDZ) 1 mg L-1, Zeatin 0.1 mg L-1 and NAA (0.01 mg L-1, 1 mg L-1). The results show that the combination of BAP 9 mg L-1 and NAA 0.01 mg L-1 produced the highest shoot induction at 12 weeks after planting. Giving zeatin 0.1 mg L-1 and NAA 1 mg L-1 produces the highest shoot length at 12 weeks after planting.PENGUJIAN MULTIPLIKASI EKSPLAN KUNYIT DENGAN PENAMBAHAN AUKSIN DAN SITOKININ PADA MODIFIKASI MEDIAPenelitian ini bertujuan untuk mendapatkan jenis dan konsentrasi sitokinin serta konsentrasi auksin yang optimal untuk multiplikasi tunas kunyit secara in vitro. Percobaan dilaksanakan pada bulan September 2017 sampai Februari 2018 di laboratorium Kultur Jaringan Teknologi Benih Fakultas Pertanian Universitas Padjadjaran. Bahan yang digunakan dalam penelitian ini adalah murashige dan skoog modified multiplication medium, agar-agar, aquades steril, HgCl2, alkohol 70%, clorox, tween 80, fungisida, dan bakterisida. Zat Pengatur Tumbuh (ZPT) yang digunakan yaitu BAP, TDZ, Zeatin, dan NAA. Sumber eksplan yang digunakan yaitu berasal dari tunas kunyit klon asal Bogor. Rancangan percobaan pada penelitian ini yaitu Rancangan Acak Lengkap (RAL) dengan tujuh perlakuan dan empat ulangan. Media tanam yang digunakan yaitu Murashige Skoog Modifikasi (MS) dengan penambahan Benzyl Amino Purine (BAP) 9 mg L-1, Thidiazuron (TDZ) 1 mg L-1, Zeatin 0,1 mg L-1, dan NAA (0,01 mg L-1, 1 mg L-1). Hasil percobaan menunjukkan bahwa kombinasi BAP 9 mg L-1 dan NAA 0,01 mg L-1 menghasilkan induksi tunas tertinggi pada 12 MST. Pemberian zeatin 0,1 mg L-1 dan NAA 1 mg L-1 menghasilkan panjang tunas tertinggi pada 12 MST.